UPAYA PREVENTIF DAN REPRESIF TERHADAP PROSTITUSI ONLINE BERDASARKAN PERATURAN PERUNDANG-UDANGAN YANG BERLAKU DI INDONESIA (Lex Journal: Kajian Hukum & Keadilan, 2018)
The crime of online prostitution is a renewal of conventional prostitution. If conventional prostitution only uses one place facility/building to run an illegitimate business. In contrast, online prostitution only uses technological, the internet that makes it easier for prospective users with male / female commercial sex workers (PSK) or between potential users with pimps, PSK service brokers. The mode used is to use the means of electronic information exchange, photo exchange, video and finally meet in one place to have intimate relationships and make payments for these services. This writing uses a normative juridical method, analyzes the laws and regulations that apply to legal phenomena, online prostitution. The Conclutions are: there are factors that cause online prostitution: 1. internal factors such as family factors and friendships; 2. External factors such as avoiding tracking officers and economic factors to obtain large amounts of money but quickly. Preventive efforts can be made through educational facilities, means of economic equality & employment in the informal sector, increasing social & cultural awareness starting from the neighborhood of Neighborhood Groups (RT), supervising boarding houses or apartments / flats so as not to be misused as a place of prostitution. Whereas the repressive efforts that can be carried out are through means of providing legal sanctions based on the prevailing laws and regulations, online prostitutes, both users of commercial sex workers, prostitutes and pimps. The purpose of the criminal sanctions is to make deterrence, so that no other people will carry out online prostitution & so that these former prisoners can be well received in society.